2001
DOI: 10.1007/pl00000916
|View full text |Cite
|
Sign up to set email alerts
|

Genes for neurotrophic factors and their receptors: structure and regulation

Abstract: Neurotrophins and their receptors have attracted much interest during the last two decades. Although the mode of action of molecules of the neurotrophin system has been studied extensively, information on molecular mechanisms governing their expression is mosaic and incomplete. This review attempts to summarize the data available on gene structure and transcriptional regulation of neurotrophins and their receptors, and outlines perspectives for the future in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
11
0
6
Order By: Relevance
“…mRNA was aligned across species using mVISTA (http://genome.lbl.gov/vista/mvista/submit.shtml), and phylogenetic trees were constructed [21][33]. NCBI's Blastn and Blastp were used to compare nucleotide and protein identities and gaps between species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA was aligned across species using mVISTA (http://genome.lbl.gov/vista/mvista/submit.shtml), and phylogenetic trees were constructed [21][33]. NCBI's Blastn and Blastp were used to compare nucleotide and protein identities and gaps between species.…”
Section: Methodsmentioning
confidence: 99%
“…As for Ntrk2, a comprehensive analysis of Ntrk2 immunoreactivity was assessed and it was found to be expressed mainly in glandular cells of the salivary gland, small intestine, colon, endocrine pancreas, bone marrow hematopoietic cells, monocytes/macrophages of the lymph nodes and spleen, and in the epidermis [15]. Previous studies have shown that neurotrophins in the brain are regulated by neuronal activity (Ca++ influx induced transcription) [16], and steroid hormones [17][20], and that tissue-specific expression is driven by multiple promoters [21].…”
Section: Introductionmentioning
confidence: 99%
“…This gene contains 16 introns of 70bp to 3.3kb and 17 exons of 18 to 394bp (Indo et al, 1997), with the 9 first exons encoding for the extracellular part of the receptor (Metsis, 2001). The TrkA protein contains 790 amino acids with a molecular weight of 140 kDa (Meakin & Shooter, 1992), and is composed of an intracellular domain containing a tyrosine-kinase intrinsic activity, a unique transmembrane helix, and an extracellular domain dedicated to NGF binding (Wiesmann & de Vos, 2001).…”
Section: Structure Of the Trka Receptormentioning
confidence: 99%
“…Owing to its role in multiple cellular activities, Trk receptor expression is regulated at the level of transcription (10), mRNA stability (11) and protein half-life (12). However, regulation of Trk receptor protein synthesis is not well understood.…”
Section: Introductionmentioning
confidence: 99%